Case report: A particularly rare case of endogenous hyperinsulinemic hypoglycemia complicated with pregnancy treated with short-acting somatostatin analog injections - Barsi, Ádám; Beke, Artúr; Sármán, Beatrix; Sarman, Beatrix (Frontiers in Endocrinology, 2022)
Hyperinsulinemic hypoglycemia is a rare disease, and only two cases complicated with pregnancy were published previously when our patient became pregnant. We introduce a successful management of a pregnancy in a patient with endogenous hyperinsulinemic hypoglycemia, a condition also known as non-insulinoma pancreatogenous hypoglycemia syndrome or earlier as nesidioblastosis. A 29-year-old female patient was treated with endogenous hyperinsulinemic hypoglycemia since the age of 4 months, getting daily 3x75 mg diazoxide – which adds up to 225 mg per day. Adequate glycemic control could be achieved with this therapy. Genetic testing and various imaging examinations were carried out earlier to specify the disease and to exclude focal forms. The patient came to the clinic with a positive pregnancy test and consequential hypoglycemic episodes. Hospital admission was needed to correct the metabolic condition. Although the patient was informed about the potential risks, she decided to carry out the pregnancy. According to the quite limited literature somatostatin analogs are the only therapy used previously during pregnancy in hyperinsulinemic hypoglycemic patients. One publication reported normal pregnancy outcome, but in another case restricted fetal growth was observed. In our case we stopped diazoxide and parallelly introduced short-acting somatostatin analog octreotide in the therapy, and further dietetic changes were proposed. Beside daily regular self-blood glucose monitoring, regular gynecological controls were carried out monthly and confirmed healthy fetal development. The patient gave birth to her first child, a well-developed female neonate, on the 38th week with cesarean section.